An Experimental Investigation of Social Norms - Mari Rege; Kjetil Telle (Statistics Norway, Research Department, 2001)
Several economists have maintained that social and internalized norms can enforce cooperation in public good situations. This experimental study investigates impacts of social and internalized norms for cooperation among strangers in a public good game. The experiment has two treatment effects. First, it reveals each person's identity and his contribution to the public good. Second, it presents the public good game in a language which suggests associations to social and internalized norms for cooperation. Both treatment effects increase voluntary contributions significantly. These results suggest two important policy tools to crowd in social and internalized norms in a public good situation.
Keywords: A13; C91; D11; H41; 330; Cooperation; Framing; Public goods; Social approval; Social norms.